Fractional order tube model reference adaptive control for a class of fractional order linear systems - Balaska, Hanane; Ladaci, Samir; Djouambi, Abdelbaki; Schulte, Horst; Bourouba, Bachir (Zielona Góra: Uniwersytet Zielonogórski)
We introduce a novel fractional order adaptive control design based on the tube model reference adaptive control (TMRAC) scheme for a class of fractional order linear systems. By considering an adaptive state feedback control configuration, the main idea is to replace the classical reference model with a single predetermined trajectory by a fractional order performance tube guidance model allowing a set of admissible trajectories.
Keywords: fractional order linear system; model reference adaptive control; fractional adaptive control; optimization; performance tube; fractional order TMRAC